An exploratory study of a work-based learning reflection module and the potential links between student attendance and engagement and student success as an indication of the mastery of reflection. Issue 6 (2nd November 2021) - Gerhardt, Trevor
ABSTRACT: Reflection is pivotal in Work-Based Learning to enable learning to be gained from experience. Effective reflection also aids self-efficacy and agency. However, more can be known regarding how reflection works in Work-Based Learning contexts and whether attendance, engagement, age and gender are important factors. An exploratory archival research complimented with an unstructured interview was conducted with a class of 27 business students studying a module on reflection on a Work-Based Learning programme. Descriptive statistics and a thematic analysis revealed that the probability of mastering reflection depended upon more than six weeks attendance as well as active engagement in reflective activities. Receiving feedback on journal entries enhanced understanding and application. Women were more likely to engage in feedback opportunities.